Impacts of utilizing swine lagoon sludge as a composting ingredient. (1st February 2023) - Patil, Piyush; Sharara, Mahmoud; Shah, Sanjay; Kulesza, Stephanie; Classen, John
Abstract: Lagoon sludge, a byproduct of swine operations in the Southeast United States, poses a management challenge due to its high mineral and metal content. Composting is a low-cost, scalable technology for manure management. However, limited information is available on composting swine lagoon sludge in terms of recipes, greenhouse gas emissions and end-product quality. Moreover, due to its high Zn and Cu content, high inclusion of sludge in composting recipes can potentially inhibit the process. To address these knowledge gaps, in-vessel aerated composting (0.4 m3each) was carried out to evaluate impacts of sludge inclusion, at 10% (Low Sludge, LS-Recipe) and 20% (High sludge, HS-Recipe) wet mass-basis, on composting process and end-product quality. Comparable maximum temperatures (74 ± 2.7 °C, 74.9 ± 2.9 °C), and organic matter loss were observed in both recipes. Similarly, sludge inclusion ratio had no significant impact on cumulative GHG emissions. The global warming potential (20-year GWP) for swine lagoon sludge composting using LS and HS recipes was observed to be 241.9 (±13.3) and 229.9 (±8.7) kg CO2-e/tDM respectively. Both recipes lost 24–28% of initial carbon (C) and 4–15% of nitrogen (N) respectively. Composting and curing did not change water-extractable (WE) phosphorus (P) concentrations while WE Zn and Cu concentrations decreased by 67–74% and 55–59% respectively in both recipes. End compost was stable (respiration rates <2 mgCO2-C/g OM/day) with germination index >93 for both recipes. Highlights: Composting lagoon sludge achieved stable and mature compost. Thermophilic temperatures attained in both recipes met disinfection requirements. Lower GHG flux and emissions were observed for both recipes. Composting poses a promising alternative for swine lagoon sludge management.